PENGARUH BOND RATING TERHADAP IMBAL HASIL SAHAM DI BURSA EFEK INDONESIA - Ahmad, Gatot Nazir; Zakaria, Mohammad (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2011)
The purpose of this study is to determine the effect of bond rating on stock returns. Sample of this study covers 20 firms listed on Indonesia Stock Exchange. The research period is from 2006 until 2008. Controlling for systematic risk, earning per share and liquidity, the result show that bond rating has insignificant effect on stock returns. This suggests the bond rating announcement has no news to the investor. Further, contrast to the theory, the coefficient of bond rating is positive meaning the higher risk the low return and vice versa. Keywords : Bond Rating, Stock Return, Liquidity